(3GdYHQ aj NHQ ef YHQs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3YHO GdYRjR Hf eMeO Hf YHO GdQMef Gdchjc GdTGaYj GdPgHjs ((3GHf MLQ GdYSbdGfi s)
(3ChdgG (B:s
(3hHYO agPG JGQjN eNJUQ Ydi GdSfhGJ , CPcQ ajg eG jbOQ di ef CTgQ GdMhGOK hGdhajGJ s
(3BNQgG (B:s
(3hbO GfJgi eG GQGOJ EjQGOg ef cHGQ GdMhGOK hCcGHQ GdfGS ef GdYdeGA hGdQhGI hGdCYjGf haQZJ efg ai SGHY YTQ Pi GdMLI SfI NeS YTQI hSHYeGFI s
(3HOCg GdeDda ef GdSfI GdChdi ddgLQI hGfJgi ajg Edi SfI (B700s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B104 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs